1996
DOI: 10.1073/pnas.93.20.11173
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the cyclin-dependent kinase 5 gene results in abnormal corticogenesis, neuronal pathology and perinatal death.

Abstract: Although cyclin-dependent kinase 5 (Cdk5) is closely related to other cyclin-dependent kinases, its kinase activity is detected only in the postmitotic neurons. Cdk5 expression and kinase activity are correlated with the extent of differentiation of neuronal cells in developing brain. CdkS purified from nervous tissue phosphorylates neuronal cytoskeletal proteins including neurofilament proteins and microtubule-associated protein tau in vitro. These findings indicate that Cdk5 may have unique functions in neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
754
1
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 855 publications
(781 citation statements)
references
References 44 publications
22
754
1
1
Order By: Relevance
“…Furthermore, Ckd5 can directly phosphorylate the microtubule-binding protein Doublecortin to mediate nuclear translocation during post-mitotic cell migration (Tanaka et al, 2004). Consistent with these results, deletion of cdk5 in mice results in lamination defects in the CNS (Ohshima et al, 1996). However, the in vivo role for Fak in nuclear migration, appears to be more complicated.…”
Section: Kinases In Nuclear Migrationmentioning
confidence: 55%
“…Furthermore, Ckd5 can directly phosphorylate the microtubule-binding protein Doublecortin to mediate nuclear translocation during post-mitotic cell migration (Tanaka et al, 2004). Consistent with these results, deletion of cdk5 in mice results in lamination defects in the CNS (Ohshima et al, 1996). However, the in vivo role for Fak in nuclear migration, appears to be more complicated.…”
Section: Kinases In Nuclear Migrationmentioning
confidence: 55%
“…Moreover, p35⅐Cdk5 appears to be important for normal neuronal function; its kinase activity increases during neurogenesis, and it is essential for neurite outgrowth during neuronal differentiation (11). A fundamental role for p35⅐Cdk5 is supported by the findings that targeted disruption of the p35 gene in the mouse leads to severe defects in laminar organization of neurons in the neocortex and cerebellum, 2 and targeted disruption of Cdk5 gene leads to abnormal corticogenesis, lesions in the central nervous system, and perinatal death (29). Although p35 shares little sequence similarity to cyclin, computer modeling predicts that p35 may fold into cyclin-like tertiary structure and activate Cdk5 in a manner similar to a cyclin (30).…”
mentioning
confidence: 63%
“…If Cdk5 function is important for neuronal differentiation, as indicated by recent evidence (11,29), then Cdk5 must be regulated by very different mechanisms compared with other cell cycle-regulating cyclin⅐CDK complexes. Cell cycle-regulating cyclins and CDKs are generally turned off during neuronal differentiation (51,52), since cell cycle arrest appears to be a prerequisite for differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…25,34 Cdk5 function is crucial in cortical development as mice lacking this serine/threonine kinase or its neuronal activator p35 display inverted layering of neurons. [36][37][38][39][40] A series of experiments demonstrated that NUDEL is likely to be a physiological substrate of Cdk5. 34 Thus it may form a link between a Cdk5 and a LIS1-mediated neuronal migration pathway.…”
Section: Nude and Nudelmentioning
confidence: 99%